Fundamentals of nanoelectronics. - Hanson, George W., ....- (Upper Saddle River : Pearson, 2008)
This guide provides an introduction to nanoelectronics, as well as a self-contained overview of the necessary physical concepts - taking a fairly gentle but serious approach to a field of growing importance. Describes the physical principles needed to understand nanoelectronic devices. Explores nanoelectronic devices that have single-electron precisions. Considers nanosolids, such as semiconductor quantum dots and nanoscopic wires. MARKET: For professionals interested in learning more about nanoelectronics.